Disfunção tubular renal associada ao tenofovir na terapia antirretroviral em portadores de HIV - Souza, Renato Ferneda de (2018)
Although the antirretroviral therapy, in spite of having reduced the mortality for AIDS and increased the lifespan of the HIV bearers, it can contribute to the arrise of adverse long time effects, besides renal ones. The tenofovir (TDF), a first line antirretroviral (ARV) for treatment, has low general toxicity. TDF can take to moderate reduction in glomerular filtration rate (GFR) and a larger prevalence of renal tubular dysfunction (RTD) when compared to those patients who are not on therapy of this medication. The decline of the renal function found in the patients can vary from mild to chronic injuries or a simple reduction in GFR. The mechanism of RTD is not completely understood, and it has been attributed to the mitocondrial lesion in the proximal tubule cells caused by the increasing of the intracelular TDF concentration. Aditionaly, host´s genetic polymorphisms have been considered one of the TDF concentration increasing causes. RTD can be characterized concisely by the deficiency in the solutes reabsorption as bicarbonate, uric acid, phosphate, glucose and low weight molecular proteins. Objectives: verify the prevalence of RTD in the HIV bearers on TDF treatment, identify the risk factors associated and compare the 24-hours urine methods with the serum creatinine and its clearance for the RTD identification. Methods: longitudinal prospective study, performed in the Complexo de Doenças Transmissíveis em São José do Rio Preto/SP, between january 2011 to december 2015. Results: 163 patients were included in the study, in which 106 (68,4%) didn't use TDF and 57 (31,6%) used TDF. RTD occured in 8 patients that used TDF, a prevalence of 14%. The patients age was identified as significant risk factor for the development of RTD. The proteinuria (average 109,2mg/24h) and the phosphaturia (average 791,9mg/24h) were significant for the diagnosis of RTD. Conclusions: the prevalence of RTD was 14%. The age was determined as risk factor for RTD, mainly in patients over 60 years-old. Phosphaturia and the proteinuria showed the greatest diagnosis sensibility for RTD, respectively. The serum creatinine and phosphorus concentration, the creatinine clearance and the stand alone hyperproteinuria should not be used as diagnosis predictors for RTD.